Laughter Under Fascism: Humour and Ridicule in Italy, 1922–43. Issue 1 (5th March 2015) - Gundle, Stephen
Abstract : This article explores the place of permitted humour in Fascist Italy and considers its implications for the historiography of Fascism. It examines different strands of humour and discusses their role in a regime that was headed by a man with little or no sense of humour and in which oppositional humour was severely punished. After the suppression of anti-fascist satirical magazines, the variety performer Petrolini and some journalists, all of whom in some measure supported the regime, injected elements of satire and parody into their work. The mainstream media offered a diet of light comedy that was designed to amuse and distract. International in character and largely devoid of references to the reality of life, it played a part in the management of social tensions. Only when disaffection began to set in the early 1940s did the derision and scorn laced with cruel humour, which had been features of Fascist humour from the outset, gain wider currency in propaganda campaigns directed against social types identified as undermining the regime. Overall, humour is seen to have reflected Fascism's ambivalent nature as a revolutionary force that supported bourgeois order.